GDP per capita vs foreign direct investment: key drivers of a country's technological leadership - Kwilinski, Aleksy (Technological and Economic Development of Economy, 2025)
This study aims to test the hypothesis that countries with high GDP per capita achieve technological leadership not primarily due to their domestic production capacity but through the inflow of foreign direct investment (FDI). The research covers 21 developed countries across Western Europe, the Americas, Asia, Africa, and Australia, for the period 2011 to 2022. The Bartlett test, Kaiser-Meyer-Olkin (KMO) criterion, and exploratory factor analysis (EFA) were employed to identify the most relevant indicators for the study. A true fixed-effects stochastic frontier model was applied to panel data, based on the Cobb-Doug- las production function and the translogarithmic function, to evaluate the determinants of technological development and identify technical efficiency. Fourteen indicators of techno- logical development were used as independent variables, while five key economic indicators were included as adjustment variables. Research and development expenditure served as the dependent variable. Three frontier models were constructed, incorporating adjustment variables such as GDP per capita, FDI net inflows, and FDI net outflows. The findings provide valuable insights for reviewing the key determinants of technological development management in economically advanced countries.First published online 17 March 2025